Digital platform of light industry Bee-online.ru as a promising channel for promoting products of Belarusian manufacturers to the market of the EAEU countries - Bezpalko, Lyudmila V. (Journal of the Belarusian State University. Economics, 2025)
The article presents the results of a study assessing the promotion of Belarusian manufacturers’ products through the Eurasian digital platform for the light industry Bee-online.ru. The article assesses the fulfillment of the Bee-online.ru digital platform’s plan for 2023 –2024 and the level of representation of Belarusian light industry enterprises on the platform as of the 3rd quarter of 2025. The article identifies the main problems that reduce the interest of foreign customers in placing orders with Belarusian light industry manufacturers. The article defines the advantages of the digital platform for both manufacturers and customers, and highlights the shortcomings of the platform’s functionality. The correctness of the online presence of Belarusian manufacturers on the platform Bee-online.ru is assessed through the analysis of their accounts and personal accounts; recommendations are provided.